Long-lasting pain-related behaviors in mouse chronic cystitis model induced by a single intravesical injection of hydrogen peroxide - Koji Dogishi; Mizuki Kodera; Shohei Oyama; Hisashi Shirakawa; Takayuki Nakagawa; Shuji Kaneko (Elsevier, 2015)
We previously established a long-lasting cystitis model by an intravesical injection of hydrogen peroxide (H2O2) into mice. In this study, we assessed the pain-related behaviors in the cystitis model. An intravesical injection of 1.5% H2O2 transiently decreased spontaneous locomotor activity at 3 h after injection, indicative of acute spontaneous pain. In contrast, licking response to a bladder distention was slowly observed as licks to the lower abdomen at 7 and 14 days after injection, which was attenuated by amitriptyline and morphine, but not by oxybutynin. These results suggest that H2O2-induced chronic cystitis model shows delayed and long-lasting painful pathological condition.